THE INFLUENCE OF EMPLOYEE COMPETENCY ON THE QUALITY OF EMPLOYEE PERFORMANCE IN THE RIAU PROVINCE DPRD SECRETARIAT - Ridha Nurhayati; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The success of an organization depends on the quality of work of employees to carry out their duties with maximum results. Competence is one of the factors that influences employee performance. Employees who have good competence will produce good performance too. Employee performance needs to be considered and improved properly to support the vision and mission goals that have been set within an organization. The research aims to determine the influence of employee competency on the quality of employee performance at the DPRD Secretariat of Riau Province. The type of research used is descriptive quantitative, with data collection techniques using questionnaires. The population in this study was 201 employees at the DPRD Secretariat of Riau Province. The sample used in this research was 67 people. The data analysis technique in this research is a simple linear regression test using SPSS V.25. The research results show that there is a significant influence of the Competency variable (X) on Performance Quality (Y) where the calculated t is 9.782 and the t table is 2.404 at a significance level of 5%. The correlation test results show that the two variables tested have a strong correlation, namely 0.772. Furthermore, by interpreting the coefficient of determination value of 59.5% which has a positive effect, it can be concluded that the higher the employee competency, the higher the quality of employee performance in that place